2010
DOI: 10.1021/jf1017862
|View full text |Cite
|
Sign up to set email alerts
|

Berry Marinades Enhance Oxidative Stability of Herring Fillets

Abstract: Marinating herring fillets in a 50 g/L powder of elderberry, cranberry, or black currant inhibited the oxidation of lipids and proteins and also the degradation of tocopherol. Cranberry and black currant appeared to be more efficient than elderberry in inhibiting the degradation of tocopherol and the formation of ammonium. Elderberry marinades provided the most significant color changes. The injection of fillets with a 5% salt solution resulted in significantly increased levels of carbonyls, ammonium, and biog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Previous studies reported reduced TBARS values in meat products containing cranberry extracts (17,22). However, Sampels et al (32) reported cranberry was not effective in inhibiting oxidation of marinating herring fillets. The present study showed no statistical differences between cranberry and BHA on TBARS formation.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies reported reduced TBARS values in meat products containing cranberry extracts (17,22). However, Sampels et al (32) reported cranberry was not effective in inhibiting oxidation of marinating herring fillets. The present study showed no statistical differences between cranberry and BHA on TBARS formation.…”
Section: Discussionmentioning
confidence: 97%
“…1-penten-3-ol has been used as an oxidation marker of n-3 PUFA fatty acids (FA) (Hansen, Mørkøre, Rudi, Langsrud, & Eie, 2009;Nordvi et al, 2007;Sampels, Åsli, Vogt, & Mørkøre, 2010); and hexanal, an oxidation marker of n-6 FA, has been found to correlate with rancid odor and off-flavor (Alghazeer, Saeed, & Howell, 2008). 3-methyl-butanal is related to protein oxidation, and Baron, Kjaersgard, Jessen, and Jacobsen (2007) suggested that the development of this volatile component could be the result of interaction between oxidized lipids and proteins in frozen trout.…”
Section: Controlmentioning
confidence: 98%
“…Liquid loss was measured using a firmness analyzer (TA‐XT Plus, Stable Micro Systems, United Kingdom) by pressing a flat‐ended cylinder (diameter, 75 mm; type P/75) into the fillet below the dorsal fin perpendicular to the muscle fibers at a speed of 2 mm/s until the cylinder reached 50% of the fillet height and held for 60 s. A dry, preweighed filter paper (seven filter papers for each sample) was placed under the sample. The filter papers were then weighed immediately after the test, with and without the fish piece, and the water loss was calculated (Sampels, Asli, Vogt, & Morkore, ).…”
Section: Methodsmentioning
confidence: 99%